PENGARUH KREATIVITAS DAN K EMAMPUAN KEWIRAUSAHAAN TERHADAP KEBERHASILAN USAHA PADA UMKM KULINER DI BATURAJA TIMUR KABUPATEN OKU - Rosmala Dewi; Tati Herlina (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2021)
This study aims to determine the influence of creativity and entrepreneurial skill on business success in culinary MSMEs in East Baturaja, OKU Regency. In conducting the analysis, multiple linear regression analysis is used with the SPSS 16.0 for windows program, showing that partially creativity has a significant influence on business success. Likewise, entrepreneurial skill has a significant influence on business success, and the R Square coefficient of determination is 0.618, it means that the percentage of contribution of creativity and entrepreneurial skill on business success is only 61.8% while the rest is influenced by other variables outside of this study such as work hard and opportunities.